Long term evaluation of the impact of autologous peripheral blood stem cell transplantation in multiple myeloma: a cost-effectiveness analysis. - Alessandro Corso (Public Library of Science (PLoS), 2013)
Background High-dose therapy with autologous peripheral stem cell transplantation represents today the standard approach for younger multiple myeloma patients. This study aimed to evaluate the long term economic impact of autologous transplantation with respect to conventional therapy. Methods We retrospectively reviewed the charts of multiple myeloma patients diagnosed at our department between 1986 and 2003 and treated according to the therapy considered standard at the time of diagnosis. Analysis of costs was done by assessing resource utilization and direct costs were measured and monetized before proceeding with the analysis, based on public health service tariffs. Results Group A including 78 patients treated with Melphalan and Prednisone was compared with Group B including 74 patients who received an autologous transplant. The median overall survival was 3.2 and 5.4 years respectively (p = 0.0002). Mean cost per patient was significantly higher in group B with respect to group A (102373€ vs 23825€; p<0.001). The final quality-adjusted-life-year gain in group B patients as compared to group A was 1.73 QALY, with an incremental cost-effectiveness ratio of 45460€. With a threshold of 75000€ per QALY gained, the cost effectiveness acceptability curve indicated that the probability that autologous transplantation in multiple myeloma is a cost-effective intervention is 90%. Conclusions The cost of autologous transplantation remains high. The calculated incremental cost-effectiveness ratio, however, given the significant prolongation of overall survival obtained with autologous transplantation, is within an acceptable threshold. Notwithstanding, its high cost should be taken into account when considering the whole cost of multiple myeloma.